Determinants of defense expenditure in South Korea / Lee So Yeon - Lee , So Yeon (2020)
This research pointed out the importance of defense spending as an „economic means‟ for national security in South Korea while due to the aftermath of US-China trade war, the threats and tension between North Korea and other neighboring countries such as China have become much more severe. In this context, an empirical study was conducted to investigate the factors determining national defense expenditure with secondary data from 1960 to 2018. The domestic factors namely economic growth, arms trade, the threat of North Korea and the Republic of Korea (ROK)-United States (US) defense alliance were established as those explanatory variables. The findings showed that the effect of threats and alliance factor on defense expenditure was important in explaining the South Korean defense expenditure. This paper suggested that strengthening the ROK-US-Japan defense alliance, promotion of Official Development Assistance, and adoption of Women's basic military training system for contributing to long-term defense security and national interests of South Korea.